Exploring student attitudes to the refugee crisis - Hempkin, Kirsten (ELOPE (Ljubljana), 2016)
The issue of migrants and refugees has occupied Europe for the last few months. Much of the discourse surrounding this issue has been overwhelmingly negative, lapsing at times into stereotype, prejudice and even hate speech. As language teachers at a humanities faculty, we have a responsibility to address this issue in the classroom, especially as classroom experience tells us that our students are prone to stereotypical thinking. The article presents a series of song-based activities intended for use in language development classes for future teachers and translators at the Faculty of Arts, University of Maribor.
Keywords: begunci; begunska kriza; medkulturno ozaveščanje; migranti; negativne javne govorice; odnos študentov; pesmi; stereotipno mišljenje